SISTEM PERINGATAN DINI KEBOCORAN GAS LPG MENGGUNAKAN SENSOR MQ-5 - Nuraharjo, Eddy; Avianto, Dimas Alif (Information Technology and Telematics, 2018)
ABSTRACT LPG (Liquefied Petroleum Gas) Gas Leak Early Warning System is a system that minimizes the danger of LPG gas leak which can lead to an explosion of LPG gas cylinders. This system was designed using a prototype method using Arduino Uno, MQ-5 sensor to detect gas levels in the room, LCD to display gas levels, buzzer as an alarm, green and red LEDs as indicators of leakage and fan to reduce gas levels in the room. This system can also be connected to an Android smartphone via an application that is connected via Bluetooth. Based on the results of the tests that have been carried out, the system can run quite well in accordance with the research objectives. This LPG Gas Leak Early Warning System is expected to minimize accidents caused by LPG gas leak which can cause explosions and fires so that LPG gas users can use LPG gas safely.